Analytical and clinical validation of a NGS panel in detecting targetable variants from ctDNA of metastatic NSCLC patients - Feifei Fan; Guozhong Jiang; Juan Lv; Hongmin Wang; Wenjie Li; Chenglin Liu; Yu Zhao; Zhou Zhang; Haiwei Du; Zhihong Zhang; Xiangnan Li; Wen‐cai Li (Cancer Medicine)
Abstract Background Circulating tumor DNA (ctDNA) has emerged as a promising biomarker for noninvasive cancer diagnostics, particularly in the context of metastatic non‐small‐cell lung cancer (NSCLC). Detecting targetable variants through ctDNA analysis offers the potential to guide treatment decisions, especially in cases where tissue samples are insufficient or unavailable. Method In this study, we developed and validated a next‐generation sequencing panel targeting 101 cancer‐related genes (101‐test) to detect somatic variants in ctDNA from a large cohort of Chinese patients with metastatic NSCLC. The performance of the 101‐test was assessed by evaluating its limit of detection (LOD), accuracy, and precision in identifying molecular variants. Additionally, the concordance between ctDNA and tissue samples for detecting targetable variants was analyzed in 904 patients. Results The 101‐test demonstrated a LOD of 0.38% for single‐nucleotide variants (SNVs), 0.33% for insertions and deletions (InDels), and 0.33% for fusions. Sensitivity was 98.3% for SNVs, 100% for InDels, and 100% for fusions when compared to digital droplet PCR (ddPCR)/breakpoint PCR reference methods. The by‐variant sensitivity for somatic variants was 97.5%, with a specificity of 99.9% between tumor‐only and tumor‐normal analyses. In a real‐world cohort, the concordance between ctDNA and tissue samples for identifying targetable variants was 72.2% (457/633). Notably, the EGFR S768I variant, recently recommended by clinical guidelines, achieved an 80% concordance rate. Furthermore, 4.3% of patients (27/633) with targetable variants were identified exclusively through ctDNA testing. Conclusion The ctDNA‐based 101‐test is a highly sensitive and specific tool for detecting targetable variants in metastatic NSCLC, particularly in cases with insufficient tissue samples. The findings support the use of ctDNA testing as a reliable and complementary method to traditional tissue‐based molecular analysis, enhancing the precision of treatment strategies for NSCLC patients.